RESOLUSI KONFLIK DALAM ISLAMIC STUDIES: PERSPEKTIF HARMONISASI ANTAR UMAT BERAGAMA RICHARD C. MARTIN - Suaidi, Suaidi (UIN Sunan Kalijaga Yogyakarta, 2024)
Disharmony among religious communities in the era of globalization has become a focal point for religious observers, as it often gives rise to complex issues in Europe, North America, and other parts of the world. This article will explore the importance of Islamic studies in understanding the complexity of relationships between Islam and other cultures and religions. It will utilize Richard C. Martin's multidisciplinary approach to Islamic studies. The research method employed is qualitative-normative, focusing on literature review and the concepts of cross-cultural dialogue and inclusivity within the context of global religious diversity. The findings of the research indicate that Martin's approach, which advocates for inclusivity and cross-cultural dialogue, is the best way to promote a deeper understanding of religions and to reduce global conflicts. Understanding the historical approach, phenomenological approach, theological approach, comparative religions approach, and structuralist approach is one of Martin's methods to achieve an inclusive interpretation of religions broadly, especially Islam. Such an understanding can lead to better global peace and cooperation. Martin's ideas offer profound insights into how Islamic studies can play a crucial role in building harmony among religious communities, particularly as a means of resolving conflicts through comparative methods. His approach underscores the need for a comprehensive understanding of the historical, social, and cultural contexts of religions to foster mutual respect and cooperation in a multicultural world. Keywords: Resolution, Conflict, Islamic Studies, Harmonization Disharmoni antar umat beragama di era globalisasi menjadi sorotan para pemerhati agama karena sering kali melahirkan persoalan kompleks seperti di Eropa, Amerika Utara maupun di belahan dunia lainnya. Artikel ini akan mengulas pentingnya studi keislaman (islamic studies) dalam memahami kompleksitas hubungan antara Islam dengan budaya dan agama lain. Artikel ini akan menggunakan pemikiran Richard C. Martin sebagai pendekatan multidisipliner dalam Islamic studies. Metode penelitian yang digunakan adalah metode kualitatif-normatif dengan mengkaji literatur Pustaka (liberary research) dan konsep dialog lintas budaya dan inklusivitas dalam konteks keberagaman religius global. Temuan dari penelitian ini menunjukkan bahwa pendekatan Martin, yang menganjurkan inklusivitas dan dialog lintas budaya, adalah cara terbaik untuk mempromosikan pemahaman yang lebih dalam tentang agama-agama dan mengurangi konflik global. Memahami pendekatan historis, pendekatan fenomenologis, pendekatan teologis, pendekatan perbandingan agama, dan pendekatan strukturalis adalah salah satu metode Martin untuk mencapai interpretasi inklusif terhadap agama-agama secara luas, khususnya Islam. Pemahaman seperti ini dapat membawa kepada perdamaian dan kerja sama global yang lebih baik. Gagasan Martin menawarkan wawasan yang mendalam tentang bagaimana studi Islam dapat memainkan peran penting dalam membangun keharmonisan di antara umat beragama, terutama sebagai sarana untuk menyelesaikan konflik melalui metode komparatif. Pendekatannya menggarisbawahi perlunya pemahaman yang komprehensif mengenai konteks sejarah, sosial, dan budaya agama-agama untuk menumbuhkan rasa saling menghormati dan kerja sama dalam dunia yang Multi-kultural. Kata Kunci: Resolusi, Konflik, Islamic Studies, Harmonisasi